2021
DOI: 10.21037/atm-21-2407
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of a totally thoracoscopic approach for reoperative mitral valve replacement: a propensity score matched analysis

Abstract: Background: This study aimed to summarize the perioperative and long-term outcomes of patients with previous mitral valve surgery (MVS) undergoing reoperative mitral valve replacement (MVR). Methods: Data for all reoperative mitral valve replacements (re-MVRs) with or without concomitant tricuspid surgery were analyzed from Guangdong Provincial People's Hospital between January 2013 and December 2019. Propensity score matching resulted in 30 matched pairs with improved balance after matching in baseline covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Likewise, mitral valvuloplasty via TTCS is superior to those via median sternotomy in terms of the rate of blood transfusion, and the incidence of sternal and wound complications [40]. Although there was no survival difference at 7-year follow-up, it has been demonstrated that the perioperative outcomes including tracheal intubation, chest tube drainage, and transfusion in the patients who underwent re-operative mitral valve replacement via TTCS is improved [41]. A re-do mitral valve procedure following TTCS is safer since there are less retrosternal adhesions [42].…”
Section: Mitral Valve Proceduresmentioning
confidence: 99%
“…Likewise, mitral valvuloplasty via TTCS is superior to those via median sternotomy in terms of the rate of blood transfusion, and the incidence of sternal and wound complications [40]. Although there was no survival difference at 7-year follow-up, it has been demonstrated that the perioperative outcomes including tracheal intubation, chest tube drainage, and transfusion in the patients who underwent re-operative mitral valve replacement via TTCS is improved [41]. A re-do mitral valve procedure following TTCS is safer since there are less retrosternal adhesions [42].…”
Section: Mitral Valve Proceduresmentioning
confidence: 99%
“…In recent years, totally thoracoscopic cardiac surgery (TTCS) has been used for coronary artery bypass grafting, resection of cardiac myxoma [ 1 ], valve replacement [ 2 ], atrial septal defect (ASD) and ventricular septal defect (VSD) closure [ 3 , 4 ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%